Mineral metabolism in male cyclists during high-intensity endurance training - Dressendorfer, R. H.; Petersen, S. R.; Moss Lovshin, S. E.; Keen, C. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
This study examined the effects of intense endurance training on basal plasma and 24-hour urinary calcium (Ca), magnesium (Mg), iron (Fe), zinc (Zn), and copper (Cu) levels in 9 male competitive cyclists. The supervised training program followed a baseline period and included a volume phase (6 weeks, averaging 87% of maximal heart rate [HRmax]), an interval phase (18 days, 100% of HRmax), and a 10-day unloading taper. The primary training outcome measure was 20-km time-trial cycling performance. Subjects ate unrestricted diets and maintained their weight. Compared to baseline, performance improved significantly (p < .05), while mineral metabolism was not significantly different after the volume phase. However, after the interval phase, renal Ca excretion increased (p < .05) and plasma Ca fell slightly below the clinical norm. As compared to the interval phase, urinary Ca decreased (p < .05), plasma Ca increased (p < .05), and performance further improved (p < .05) after the taper. Whereas Mg, Fe, Zn, and Cu metabolism remained unchanged throughout the study, greater renal Ca excretion was associated with very high intensity interval training.